The Effect Of Granting Acanthus ilicifolius Leaf Topical Methanol Extracts To The Amount Of Macrofags In Healing Of Oral Candidiasis Models With Immunosupression Condition - Ghora Setyawan; Dwi Andriani; Diana Soesilo (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2019)
Background: Corticosteroid has a strong anti-inflammatory effect, unfortunately long-term usege of corticosteroid drugs can suppressed immune system. This condition makes Candida albicans as an opportunistic phatogen caused Oral Candidiasis. Macrophages have an important role in the first defense against infection. Methanol extract of A.ilicifolius leaf has anti-fungal, anti-inflammatory compounds to fight the growth of Candida albicans. Purpose: To determine the effect of methanol extract of A.ilicifolius leaf theraphy to the amount of macrophages in the healing pricess of oral candidiasis models with immunosuppressed conditions. Materials and Method: This study was true experimental with post test only control group design. Thirty-six strain wistar, 3 months old, and 250 grams of weight which were given dexamethason 0.5 mg and tetracycline 0.5mg for 7days, after Candida albican(ATCC10231) was induced for 2 weeks (3 times/week). Rats were divided into 6 groups: untreated(K-), nystatin(K+), A.ilicifolius 8%(P1), A.ilicifolius 12%(P2), A.ilicifolius 16%(P3), A.ilicifolius 20%(P4 ) all groups were treated for 2 weeks. After being treated, the rats tongue biopsied to examine the macrophages with Haematoxylin-eosin staining and observed with microscope (400x magnification). Data analyzed statistically by One-way ANOVA. Results: the amount of macrophages at K+(47.60±4.16), P4(40.20±3.56), P3(36.20±1.92), P2(17.00±2.45) were greater than K-(15.60±4.56), P1(14.60±2.70). there are no significant difference between group K- with P1 and P2, P3 with P4. There are significant difference between group K- with K+, K- with P3 and P4. K+ with P1, P2, P3 and P4. Group P1 with P3 and P4. Group P2 with P3 and P4. Conclusion: A.ilicifolius extract can increase the amount of macrophages in oral candidiasis immunosuppression models.